Ocean Literacy Competency in Vocational Education in the Perspective of Blue Curriculum: A Document Analysis - Triastity, Sarinah; Widiaty, Isma; Handayani, Mustika Nuramalia (Journal of Vocational Education Studies, 2024)
Blue Curriculum is a new paradigm in curriculum development that utilizes ocean potential as the main basis for learning. Education is considered an easy and effective way to address the negative impacts of human activities on the marine environment. All aspects of vocational education are equipped with knowledge and skills that support sustainable development goals (SDGs), especially to reduce the negative impacts caused by human activities on the environment through sustainable and environmentally friendly practices. Vocational education is closely related to the competencies that graduates must possess. To realize the blue curriculum in vocational education, knowing the ocean literacy competencies that vocational education graduates must possess is necessary. Content analysis of the two documents found that vocational education competencies under the themes of Critical Thinking, Hard Skills, Technology, Soft Skills, and Market Orientation are present in both marine literacy documents and can be integrated into vocational education. These competencies aim for vocational education graduates to have the ability to understand the role of the ocean, respond to ocean challenges with innovative ideas, and participate in sustainability solutions.